DEMOKRASI ALA ‘INCUMBENT’ - Oktafiani Catur Pratiwi (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Direct elections to a new arena for the elite fighting old and new elites to be of power in the region. The strategy of the regional head candidate to survive and win the fight done in several ways including the popularity of capital owned by the incumbent candidate. Election as one of the requirements in procedural democracy hijacked by the incumbent candidate for creating the image of a region said to be 'democratic'.